Aplikasi Eco-Enzyme sebagai Bahan Pembuatan Sabun Antiseptik Cair yang Ramah Lingkungan: Application of Eco-Enzyme as an Ingredient for Making Environmentally Friendly Liquid Antiseptic Soap - Kurniati, Ety; Adelia, Kadek Ayu Cintya; Dwinanda, Indah Gumilang; Suprayogi, Thathit; Ayu, Regina Wahyudyah Sonata (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Household waste tends to end up in landfills as waste and can damage the environment, but with good management, it can be processed into materials with economic value. Waste materials such as vegetable waste or fruit peels can be processed into a multipurpose eco-enzyme liquid. Eco-enzyme is an organic compound in the form of a complex solution produced from the fermentation process of waste materials in the form of fruit and vegetable peels. How to make it is very easy and can be done by anyone. Because of its content, eco enzyme has many ways to help the natural cycle such as cleaning polluted water. This eco-enzyme can be used as an ingredient in making liquid antiseptic soap. This liquid antiseptic soap is the right solution to reduce water pollution in the environment. This community service activity was carried out to provide insight to mothers on increasing the utility value of organic waste through the application of eco-enzyme as a raw material for making antiseptic soap. Based on the results of organoleptic tests, the antiseptic soap produced has an aroma, color, moisture, viscosity, smoothness, and amount of foam that is liked by the community. This is proven by the organoleptic test, where the average percentage of very like and like was 100%.